High-Content Screening in Zebrafish Identifies Perfluorooctanesulfonamide as a Potent Developmental Toxicant - Dasgupta, Subham (Environ Pollut, 2019)
Per- and polyfluoroalkyl substances (PFASs) have been used for decades within industrial processes and consumer products, resulting in frequent detection within the environment. Using zebrafish embryos, we screened 38 PFASs for developmental toxicity and revealed that perfluorooctanesulfonamide (PFOSA) was the most potent developmental toxicant, resulting in elevated mortality and developmental abnormalities following exposure from 6 to 24 h post fertilization (hpf) and 6 to 72 hpf. PFOSA resulted in a concentration-dependent increase in mortality and abnormalities, with surviving embryos exhibiting a >12-h delay in development at 24 hpf. Exposures initiated at 0.75 hpf also resulted in a concentration-dependent delay in epiboly, although these effects were not driven by a specific sensitive window of development. We relied on mRNA-sequencing to identify the potential association of PFOSA-induced developmental delays with impacts on the embryonic transcriptome. Relative to stage-matched vehicle controls, these data revealed that pathways related to hepatotoxicity and lipid transport were disrupted in embryos exposed to PFOSA from 0.75 to 14 hpf and 0.75 to 24 hpf. Therefore, we measured liver area as well as neutral lipids in 128-hpf embryos exposed to vehicle (0.1% DMSO) or PFOSA from 0.75 to 24 hpf and clean water from 24 to 128 hpf, and showed that PFOSA exposure from 0.75 to 24 hpf resulted in a decrease in liver area and increase in yolk sac neutral lipids at 128 hpf. Overall, our findings show that early exposure to PFOSA adversely impacts embryogenesis, an effect that may lead to altered lipid transport and liver development.